Assessing the Effectiveness of Robotic-Based Computer Simulations in Teaching Complex Scientific Concepts in Stem Education in Nigeria (American Journal of Data Science and Artificial Intelligence, 2025)
This study investigates how well robotic-based computer simulations improve the instruction and learning of difficult scientific ideas in STEM education in South West Nigeria’s higher education institutions. The study investigates how the growing integration of artificial intelligence and robotics in educational technology affects students’ cognitive performance, conceptual understanding, and participation. Using a mixed-methods approach, qualitative data from interviews and observations blended with quantitative data from pretest-posttest evaluations. Using multi-stage sampling, three states produced a sample of 204 respondents; 192 students and 12 professors. Data were gathered using a Structured Interview Schedule (SIS), a proven Robotic Simulation-Based Science Achievement Test (RSSAT), and by observing classrooms; these tools had a reliability score of 0.82. With a mean gain score of 43.9 vs. 18.10 in the control group, the results showed a notable improvement in conceptual knowledge and academic performance for the experimental group. Statistical analysis verified a statistically significant variation in post-test results (p < 0.05), so validating the value of simulations. Though issues like initial software navigation difficulties and unreliable infrastructure were recognised, qualitative studies highlighted more student involvement, motivation, and ease of learning complicated topics. The study comes to the conclusion that robotic-based computer simulations are a very successful pedagogical tool for improving STEM teaching in Nigerian higher institutions, making difficult scientific topics more accessible and hence promoting more profound learning. One of the recommendations is for technical professionals and lecturers to schedule regular seminars and training courses to enhance their understanding of how to use simulation technology properly. Additionally, government and institutional authorities should invest in digital infrastructure, including high-speed internet, robotics kits, and licences for simulation tools.